2011
DOI: 10.1093/humrep/der324
|View full text |Cite
|
Sign up to set email alerts
|

Developmental assessment of human vitrified-warmed blastocysts based on oxygen consumption

Abstract: The respiratory rate of vitrified blastocysts after warming was significantly lower than non-cryopreserved blastocysts. Oxygen consumption of blastocysts with high developmental potential was restored earlier than that of blastocysts with low developmental potential. The results of this study suggest that it is possible to select vitrified-warmed blastocysts with high developmental potential based on their respiratory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 23 publications
3
46
0
Order By: Relevance
“…We included blastocysts whose degree of expansion was categorised as BL4/5, whose inner cell mass (ICM) was categorized before freezing as A or B, and whose trophectoderm (TE) grade was categorized before freezing as B or C, according to Gardner's criteria [8]. To obtain a numerical blastocyst morphology grading system based on Gardner's criteria, the blastocyst grade was converted to the multiplicative blastocyst quality score (BQS) [27,33]. The BQS is a measure of blastocyst quality based on established morphologic criteria, and is defined as the product of the degree of embryo development and ICM and TE grades, where grade A is given the value 3; grade B is 2; and grade C is 1.…”
Section: Study 2: Cell Membrane Damage After Vitrificationmentioning
confidence: 99%
“…We included blastocysts whose degree of expansion was categorised as BL4/5, whose inner cell mass (ICM) was categorized before freezing as A or B, and whose trophectoderm (TE) grade was categorized before freezing as B or C, according to Gardner's criteria [8]. To obtain a numerical blastocyst morphology grading system based on Gardner's criteria, the blastocyst grade was converted to the multiplicative blastocyst quality score (BQS) [27,33]. The BQS is a measure of blastocyst quality based on established morphologic criteria, and is defined as the product of the degree of embryo development and ICM and TE grades, where grade A is given the value 3; grade B is 2; and grade C is 1.…”
Section: Study 2: Cell Membrane Damage After Vitrificationmentioning
confidence: 99%
“…Differences in OC rates between fresh and vitrified-warmed blastocysts were also reported, with higher OC in the formers (64). In addition, in vitrified-warmed blastocysts it has been found that OC was restored earlier in hatching or hatched compared to arrested or degenerated blastocysts, suggesting that it could be possible to identify vitrified-warmed blastocysts with high developmental potential on the basis of their respiratory activity (64). In another retrospective study (65), 47,741 OC measurements were performed on 575 injected oocytes obtained in 56 egg donation cycles whit embryo transfer on day-3, with the aim to evaluate the correlation of OC with embryo development and clinical outcomes.…”
Section: Oxygen Consumptionmentioning
confidence: 86%
“…In human, OC was demonstrated to be a quality marker of oocyte competence being affected by maternal age and basal FSH concentration (62) or ovarian stimulation protocols (63). Differences in OC rates between fresh and vitrified-warmed blastocysts were also reported, with higher OC in the formers (64). In addition, in vitrified-warmed blastocysts it has been found that OC was restored earlier in hatching or hatched compared to arrested or degenerated blastocysts, suggesting that it could be possible to identify vitrified-warmed blastocysts with high developmental potential on the basis of their respiratory activity (64).…”
Section: Oxygen Consumptionmentioning
confidence: 99%
“…Furthermore, the oxygen uptake by vitrified bovine blastocysts, 18 hours after thawing, was the same as that of the non‐vitrified blastocysts. Another study has found that, after 6 hours, the oxygen consumption rate of the vitrified and the heated human blastocysts in the hatched group had recovered to that exhibited by the fresh blastocysts 21, 22…”
Section: Effect Of Freezing and Thawing In Assisted Reproductive Techmentioning
confidence: 99%